Comprehensive analysis of bioactive compounds in Crocus sativus stamens extracts by HPLC-DAD: investigating antidiabetic activity via in vitro, in vivo, and molecular docking simulation - Mamri, Samira; Daoudi, Nour Elhouda; Baraich, Abedellah; Ouahhoud, Sabir; Khoulati, Amine; Choukri, Mohammed; Asehraou, Abdeslam; Bnouham, Mohamed; Jaouadi, Bassem; Abousalham, Abdelkrim; Dabiellil, Fakhreldeen; Salamatullah, Ahmad Mohammad; et al. (Frontiers in Chemistry, 2024)
Introduction: Medicinal herbs used in traditional diabetes treatment are a rich source of anti-diabetic compounds. Pancreatic α-amylase inhibitors offer an effective strategy to reduce postprandial hyperglycemic levels via control of starch degradation. In this context, our study for the first time investigates the effect of Crocus sativus stamens extracts on α-amylase inhibition. Material and methods: The hydromethanolic and hydroethanolic extracts were obtained by macerating the dried stamen powder with methanol/water or ethanol/water, respectively. The total phenolic content of the stamen extracts was assessed using the Folin-Ciocalteu reagent method, while the total flavonoid content was determined using the Aluminum Chloride method. Phytochemicals were further quantified and identified using HPLC-DAD. For evaluation of hypoglycemic activity, in vitro α-amylase enzyme inhibition was calculated. The results were confirmed in vivo using an oral starch tolerance test in both normal and diabetic rats. Results: Our findings demonstrated a higher level of polyphenols and flavonoids in the hydroethanolic extract. Important flavonoids found were kaempferol, rutin, and vanillic acid, while prominent carotenoids contained trans- and cis-crocins. The in vitro study showed that both hydromethanolic and hydroethanolic extracts had considerable inhibitory effects, with maximum inhibitions of approximately 83% and 89%, respectively. In vivo tests indicated that both extracts effectively lowered peak blood glucose and area under the curve in both normal and diabetic rats following oral starch treatment. The obtained results are also supported by a docking study. Conclusion: These findings imply that C. sativus stamens possess a distinctive capability to reduce postprandial blood glucose levels. This effect is likely mediated through the inhibition of α-amylase, presenting a novel dietary avenue for managing diabetes.